Effect of DC on Herniated Group and Non-herniated Group in MCA Infraction - Seeruch, Atinart; Sitthimongkon, Ueaungkun; Muenpa , Roungtiva (Thai Journal of Neurological Surgery, 2025)
Introduction: Middle Cerebral Artery (MCA) infraction has a high mortality rate of 70-80%. Conser-vative treatment tends to ineffective. Decompressive Craniectomy (DC) can reduce mortalty rate. But at 72hours post - stroke onset is not different from conservative treatment. Objective: This study assessed the effect of waiting time for decompressive craniectomy for MCA infraction on patients' mortality rate and a good outcome (MRS < 3) at 6, 12 and more than 12 months following surgery. Methods: This study was a retrospectively reviewed medical records between 2011- 2017 of pa-tients who were diagnosed with MCA infraction and undenvent decompressive craniectomy. The primay was a mortality rate at discharge and the secondary outcome was good outcome (MRS < 3) at 6, 12 and morethan 12 months following surgery. Data were analyzed by descriptive analysis, Student t-test, Rank Sumtest, Exact Probability test, Logistic Regression and Predictive model. A P value of 0.05 was considered statistically significant. Results: Of 31 patients, there were 12 patients with clinical herniation and 19 patients with non-clinical herniation. The mortality rates of cal and non-clinical patients at discharge were 33.3% and26.3%, respectively. The mortality rates depend on waiting time for decompressive craniectomy. Good outcome was inversely proportional to the wating time for surgery. Decompressive craniectomy at 48-hourpost stroke, the non-herniated group has a better outcome than the herniated group. (MRS 3 at 6, 12,and more than 12 months are 53% vs. 24%, 58% vs. 18% and 62% vs. 2%, 2%, respectively). Conclusion: Early decompressive craniectomy can reduce mortality and increase good outcome espe-cially in the non-hermiated group. This finding can be applied to clinical practice for MCA infraction patients in order to improve the patient outcome. Further studled in prospective manner with larger number of patients may provide more information on this important issue.